In vivo relationship between near-infrared spectroscopy-detected lipid-rich plaques and morphological plaque characteristics by optical coherence tomography and intravascular ultrasound: a multimodality intravascular imaging study. (28th January 2020) - Zanchin, Christian; Ueki, Yasushi; Losdat, Sylvain; Fahrni, Gregor; Daemen, Joost; Ondracek, Anna S; Häner, Jonas D; Stortecky, Stefan; Otsuka, Tatsuhiko; Siontis, George C M; Rigamonti, Fabio; Radu, Maria; et al.
Abstract: Aims: We assessed morphological features of near-infrared spectroscopy (NIRS)-detected lipid-rich plaques (LRPs) by using optical coherence tomography (OCT) and intravascular ultrasound (IVUS). Methods and results: IVUS-NIRS and OCT were performed in the two non-infarct-related arteries (non-IRAs) in patients undergoing percutaneous coronary intervention for treatment of an acute coronary syndrome. A lesion was defined as the 4 mm segment with the maximum amount of lipid core burden index (maxLCBI4mm ) of each LRP detected by NIRS. We divided the lesions into three groups based on the maxLCBI4mm value: <250, 250–399, and ≥400. OCT analysis and IVUS analysis were performed blinded for NIRS. We measured fibrous cap thickness (FCT) by using a semi-automated method. A total of 104 patients underwent multimodality imaging of 209 non-IRAs. NIRS detected 299 LRPs. Of those, 41% showed a maxLCBI4mm <250, 39% a maxLCBI4mm 251–399, and 19% a maxLCBI4mm ≥400. LRPs with a maxLCBI4mm ≥400, as compared with LRPs with a maxLCBI4mm 250–399 and <250, were more frequently thin-cap fibroatheroma (TCFA) (42.1% vs. 5.1% and 0.8%; P < 0.001) with a smaller minimum FCT (80 μm vs. 110 μm and 120 μm; P < 0.001); a higher IVUS-derived percent atheroma volume (53% vs. 53% and 44%; P < 0.001) and a higher remodelling index (1.08 vs. 1.02 and 1.01; P < 0.001). MaxLCBI4mm correlated with OCT-derived FCT ( r = 0.404; P < 0.001) and was the best predictor for TCFA with an optimal cut-off value of 401 (area under the curve = 0.882; P < 0.001). Conclusion: LRPs with increasing maxLCBI4mm exhibit OCT and IVUS features of presumed plaque vulnerability including TCFA morphology, increased plaque burden, and positive remodelling.